2021
DOI: 10.1158/1535-7163.mct-20-0748
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Mediate the Antitumor Effects of the Oncolytic Virus HSV1716 in Mammary Tumors

Abstract: Oncolytic viruses (OV) have been shown to activate the anti-tumor functions of specific immune cells like T cells. Here, we show OV can also reprogram TAMs to a less immunosuppressive phenotype. Syngeneic, immunocompetent mouse models of primary breast cancer were established using PyMT-TS1, 4T1 and E0771 cell lines and a metastatic model of breast cancer was established using the 4T1 cell line. Tumor growth and overall survival was assessed following intravenous administration of the OV, HSV1716 (a modified h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Valproic acid, an FDA-approved anti-epileptic agent with histone deacetylase inhibitory function, is also in development for treating cancer and prevents the transcriptional activity of IFN-stimulated genes [ 91 ]. Furthermore, while commonly applied clodronate liposomes non-specifically deplete macrophages, also disabling their indirect anti-cancer activity [ 111 ], a novel, more selective agent could, for instance, interfere with systemic macrophage function or characteristic phagocytosis pathways in receptor-mediated viral clearance. However, insights suggest an important role for macrophages as cellular carriers of OVs and indicate that initial restriction of systemic macrophage functions may also have unpredicted negative effects on therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valproic acid, an FDA-approved anti-epileptic agent with histone deacetylase inhibitory function, is also in development for treating cancer and prevents the transcriptional activity of IFN-stimulated genes [ 91 ]. Furthermore, while commonly applied clodronate liposomes non-specifically deplete macrophages, also disabling their indirect anti-cancer activity [ 111 ], a novel, more selective agent could, for instance, interfere with systemic macrophage function or characteristic phagocytosis pathways in receptor-mediated viral clearance. However, insights suggest an important role for macrophages as cellular carriers of OVs and indicate that initial restriction of systemic macrophage functions may also have unpredicted negative effects on therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that tumour-resident macrophages increase in number and gain more M1 characteristics upon treatment with OVs in divergent mouse models, including oncolytic adenovirus in orthotopic GBM models [ 43 , 109 ] and anaplastic thyroid carcinoma xenograft models [ 110 ], as well as oncolytic HSV-1 in athymic and syngeneic models for GBM, breast cancer, and melanoma [ 57 , 97 , 111 , 112 , 113 ]. Moreover, tumour cell death mediated by the oncolytic mumps and measles paramyxoviruses was shown to be affected by monocyte-derived macrophage responses in murine breast cancer models irrespective of the polarisation state of the initial TAM population [ 114 ].…”
Section: Ov-induced Macrophage-mediated Responsesmentioning
confidence: 99%
“…In syngeneic, immunocompetent mouse models of primary breast cancer, the OV HSV1716, a modified HSV, reprogrammed TAMs toward a pro-inflammatory and perivascular phenotype, decreasing the prevalence of "tumor promoting" perivascular macrophages. Moreover, HSV1716 significantly increased the number of F4/80 TAM expressing proinflammatory, M1-like markers, IL-12 and iNOS, and reduced the expression of the M2-like marker MRC1 [52].…”
Section: Modulation Of Macrophage Phenotype By Ovsmentioning
confidence: 94%
“…HSV1716 inhibited mouse intracranial Harding–Passey melanoma, with HSV staining 7 days post-injection restricted to the tumors [ 38 ]. In mouse orthotopic breast cancer models HSV1716 inhibited tumor growth and metastases after intravenous administration, which was associated with increased activated CD8 + T cells, decreased Tregs, and the reprogramming of tumor-associated macrophages (TAMs) to a pro-inflammatory M1-like phenotype [ 45 ]. It was the first oHSV to enter clinical trials in Europe in a phase I trial for patients with recurrent glioma [ 92 ].…”
Section: Generation Of Ohsvmentioning
confidence: 99%